METODE EXPONENTIAL SMOOTHING EVENT BASED (ESEB) DAN METODE WINTER’S EXPONENTIAL SMOOTHING (WES) UNTUK PERAMALAN JUMLAH PENUMPANG TIBA DI PELABUHAN PENYEBERANGAN GORONTALO - Payu, Muhammad Rezky Friesta; Nurwan, N. (PATTIMURA UNIVERSITY, 2019)
Forecasting the number of passengers can be a consideration for managers of Gorontalo Crossing Port regarding the provision of tickets. The number of passengers can be influenced by certain seasonal or special events. To see the special events that affect the number of passengers arriving at Gorontalo Crossing Port, the forecasting method used is the Exponential Smoothing Event Based (ESEB) method. The seasonal influences can be known through historical data patterns and using the Winter’s Exponential Smoothing (WES) method. After compared, the ESEB method is a better method of forecasting the number of arriving passengers at Gorontalo Crossing Port because it has a smaller MAPE value than the WES method.